QOS Aware Self Adaptable Virtual Machines Management System for Cloud Computing - Selvin Paul Pete, J.; Mahadevan, G.; Selvakumar, S. (International Journal of Engineering and Technology, 2018)
Cloud Computing as of now is the most important distributed environment because of low level user management and system integration. But most important challenge cloud computing faces is effective resource provisioning, Solving the issue will result in effective consumption of service offered, better user satisfaction and resources for more people during peak hours, reduce operational burden to cloud service providers and less pay to clients. Current works are aimed at determining the usage, VM (Virtual Machine) establishment and setting up. The above process requires considerable time to construct and kill VMs which may be used to cater more user. So here we have provided, a Quality of Service Aware Virtual Machine management mechanism for creating new VMâ€™s that makes use of the system resources efficiently. The existing VM for related type of requests are identified to minimize VM creation time. In our system, QOS is guaranteed by making all tasks adhere to the SLA necessities. Services are divided using need of the hour and the critical job is given higher significance. The experimental results show that a large number of users are serviced in relation to others algorithm which will fulfil clients needs during the peak traffic.Â Â